Engineering the fitness of older patients for chemotherapy: An exploration of Comprehensive Geriatric Assessment in practice. (March 2014) - McCarthy, Alexandra L; Cook, Peta S; Yates, Patsy
Clinicians often report that currently available methods to assess older patients, including standard clinical consultations, do not elicit the information necessary to make an appropriate cancer treatment recommendation for older cancer patients. An increasingly popular way of assessing the potential of older patients to cope with chemotherapy is a Comprehensive Geriatric Assessment. What constitutes Comprehensive Geriatric Assessment, however, is open to interpretation and varies from one setting to another. Furthermore, Comprehensive Geriatric Assessment's usefulness as a predictor of fitness for chemotherapy and as a determinant of actual treatment is not well understood. In this article, we analyse how Comprehensive Geriatric Assessment was developed for use in a large cancer service in an Australian capital city. Drawing upon Actor–Network Theory, our findings reveal how, during its development, Comprehensive Geriatric Assessment was made both a tool and a science. Furthermore, we briefly explore the tensions that we experienced as scholars who analyse medico-scientific practices and as practitioner–designers charged with improving the very tools we critique. Our study contributes towards geriatric oncology by scrutinising the medicalisation of ageing, unravelling the practices of standardisation and illuminating the multiplicity of 'fitness for chemotherapy'.